(untitled) (Research, Society and Development, 2021)
Objective: analyze the occurrence and determinants of anemia and parasitosis in residents of river communities in the Amazon region. Methods: Between 2016 and 2017, biological samples and socioeconomic, food and health data were collected from 213 individuals living in the communities of Maracujá and Murucutum. Hematological analyzes of the total erythrocyte count, hemoglobin, hematocrit, VCM (Mean Corpuscular Volume), HCM (Mean Corpuscular Hemoglobin), CHCM (Mean Corpuscular Hemoglobin Concentration), RDW (Redcell volume Distribution Width), total leukocytes and platelets were performed. Stool samples were analyzed for investigation of helminths and protozoa. Results: Of the 213 subjects, only 4.70% (10) did not present any of the studied conditions. In the hematological analysis, 22% (47) presented anemia, with 23 microcytic and hypochromic and 24 normocytic and normochromic. 93% (198) of the studied subjects were infected with intestinal parasites. In the analysis of the association between the occurrence of parasitosis and anemia, 19.71% (42) individuals had both conditions. Conclusion: The diet based on açaí, beef and fish provides the studied population with protection against food-borne anemias, while parasites and anemias associated with these are high due to the precarious conditions of hygiene and basic sanitation in this population.